1986
DOI: 10.1161/01.cir.74.6.1217
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein cholesterol and coronary heart disease in hypercholesterolemic men: the Lipid Research Clinics Coronary Primary Prevention Trial.

Abstract: Plasma levels of high-density lipoprotein cholesterol (HDL-C) at entry and subsequent changes from these baseline levels were inversely predictive of coronary heart disease (CHD) end points in hypercholesterolemic men followed for 7 to 10 years in the Lipid Research Clinics Coronary Primary Prevention Trial, especially in the 1907 participants receiving cholestyramine. When the men in this cohort were compared, each 1 mg/dl increment in baseline HDL-C (mean 44.3 mg/dl) was associated with a 5.5% decrement in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
8

Year Published

1990
1990
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(94 citation statements)
references
References 17 publications
1
85
0
8
Order By: Relevance
“…19 A subsequent report from this same study demonstrated a 5.5% reduction in coronary events for every 1 mg/dl increase in HDL cholesterol. 20 This was confirmed in the Helsinki heart study as well. 21 Two recent studies have demonstrated …”
Section: -15supporting
confidence: 55%
“…19 A subsequent report from this same study demonstrated a 5.5% reduction in coronary events for every 1 mg/dl increase in HDL cholesterol. 20 This was confirmed in the Helsinki heart study as well. 21 Two recent studies have demonstrated …”
Section: -15supporting
confidence: 55%
“…Epidemiologic studies and studies in animals suggest that raising the levels of HDL cholesterol may retard the development of atherosclerosis. In humans, each increase in baseline HDL cholesterol of 1 mg per deciliter (0.03 mmol/l) is associated with 6 percent decrease in the risk of death from coronary disease or myocardial infarction (Gordon et al 1986). Data from large-scale clinical trials with statins and fibrates indicate that observed clinical benefits are related, at least in part, to improvements in HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous population studies have demonstrated an inverse relationship between plasma HDL levels and cardiovascular disease risk, establishing low HDL levels as a strong independent marker for atherosclerosis (192)(193)(194). Both the hepatic production rate and peripheral catabolism of apoA-I can influence plasma levels of HDL, and it is unclear to what extent these two different mechanisms contribute to low HDL levels during inflammation.…”
Section: Apoa-imentioning
confidence: 99%